Comunidade de formigas (Hymenoptera: formicidae) em cultivo de videiras no município de São Roque - São Paulo - Picelli, Amanda Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The cultivation of grapes is one of the most traditional cultures and the world's oldest one. In Brazil, cultivars occupy an area of approximately 90 thousand hectares, covering the south, southeast and northeast, in latitudes ranging from 30 º 56 '15''S up to 5 º 11' 15''S. The culture of the vine may be the target of the attack of some diseases and pests, and currently the main concern for growers is the subterranean mealybug, Eurhizococcus brasiliensis (Hemiptera: Margarodidae), known as pearl-ground. This arthropod infests the roots causing a progressive languish of the vine, even causes its death. In southern Brazil it is known that some species of ants can disperse pearl-ground for short distances, however, there is no information about that in the State of Sao Paulo. Thus, it is extremely important to perform studies with this focus on wine regions in this State. Therefore, this study aimed to identify the species of underground ant community in different grape varieties found in vineyards in the town of São Roque – SP, Brazil. With that purpose, samples were collected within one year. We used underground pitfalls spread across twelve points. In each of the points were placed two traps, one containing honey and the other containing sardine as attractive. The results revealed the presence of three morphospecies of ants in Niágara Rosada and four in other grape varieties, there was no significant difference in the species richness among the cultivars (Kruskal-Wallis - 0.33, p = 0.5). In both trials, the most frequent species was Brachymyrmex sp.4, suggesting that there is no dominance of distinct species of Niágara Rosada and the other grape varieties. There was no dissimilarity in species richness of the ones visiting honey or sardines (Kruskal-Wallis - 0.08, p = 0.7) and the analysis of variance indicated a great similarity in species richness between the rainy and dry seasons (Kruskal-Wallis - 0.09, p = 0.7)

O cultivo de uva é uma das culturas mais tradicionais e mais antigas do mundo. No Brasil os cultivares ocupam uma área de aproximadamente 90 mil hectares, abrangendo as regiões sul, sudeste e nordeste, em latitudes que variam de 30º 56’ 15’’S até 5º 11’ 15’’S. A cultura da videira pode ser alvo do ataque de algumas doenças ou pragas e, atualmente, a principal preocupação dos viticultores é a cochonilha subterrânea, Eurhizococcus brasiliensis (Hemiptera: Margarodidae), conhecida como pérola-da-terra. Este artrópode infesta as raízes provocando um definhamento progressivo da videira, até causar a sua morte. Na região sul do Brasil, é sabido que algumas espécies de formigas podem dispersar a pérola-daterra por curtas distâncias, entretanto, não há informações a esse respeito no Estado de São Paulo. Desta maneira, é de extrema importância a realização de estudos sob esse enfoque em regiões vinícolas deste Estado. Assim, o presente estudo teve como objetivo, identificar as espécies da mimercofauna de subsolo, em diferentes variedades de uvas presentes em parreirais na cidade de São Roque. Para isso, foram realizadas coletas no período de um ano. Foram utilizados “pitfalls” subterrâneos espalhados por doze pontos. Em cada um dos pontos foram colocadas duas armadilhas, uma contendo mel e a outra contendo sardinha como atrativo. Os resultados revelaram a presença de três morfoespécies de formigas na cultivar Niágara Rosada e quatro nas demais variedades, não havendo diferença significativa na riqueza de formicídeos entre as cultivares (Kruskal-Wallis – 0,33; p=0,5). Em ambos os plantios, a espécie mais frequente foi Brachymyrmex sp.4, o que sugere que não há dominância de espécies distintas entre Niágara Rosada e as demais variedades.Não houve dissimilaridade na riqueza de espécies que visitam mel ou sardinha (Kruskal-Wallis – 0,08; p=0,7) e a análise de variância indicou uma grande ...
Keywords: Uva - Cultivo; Formiga; Videira; Doenças e pragas; São Roque (SP)